Therapeutic hypothermia in the neonate – from best research to best practice. (7th June 2011) - Austin, T; Baron, M; Shanmugalingam, S; Broster, S
Abstract : Background: Therapeutic hypothermia is recommended as the standard of care for the management of hypoxic-ischaemic encephalopathy (HIE) (REF). The true value of clinical trials lies in their translation into universal practice. Aim: To ensure that all infants with HIE in the East of England receive the same standard of care with regard to therapeutic hypothermia. Methods: A regional Neonatal Neuroprotection Team was created to develop a coordinated service for the management of these infants and their families. The project's focus in the first year was to ensure early identification and effective initiation of cooling in eligible infants and safe transfer to one of the three regional NICUs. Initial benchmarking was followed by a programme of education and training of key stakeholders. Improvement was measured through an on-going rolling audit. Results: 53 infants were cooled in the region between October 2009 and October 2010. Passive cooling was initiated prior to transfer in all outborn infants (n=36). Throughout the year we have seen a continuing trend of earlier referral for cooling and earlier achievement of target temperature. 13 out of the 36 infants were overcooled by 0.6 (0.6–1.6) degrees. We need to balance any continued emphasis on cooling against this measure. Conclusion: By developing a regional approach to neuroprotection we are progressing towards our goal that all eligible infants receive treatment in an expedient manner. Our key to success has been through the engagement of healthcare professionals and families; testing, evaluating and adapting processes will ensure changes in practice are effective.